2022
DOI: 10.3390/fishes7050300
|View full text |Cite
|
Sign up to set email alerts
|

Larval Retention and Homing Behaviour Shape the Genetic Structure of the Bullet Tuna (Auxis rochei) in the Mediterranean Sea

Abstract: Background: The bullet tuna (Auxis rochei) is an epipelagic fish with a worldwide distribution that is highly targeted by fisheries. Genetic diversity and population genetics are good indicators of population structure and thus, essential tools for fisheries management. Knowing which factors (biotic and abiotic) might be shaping such structure is crucial for management plans. In the present study, we assessed the population structure of the bullet tuna in the western and central Mediterranean Sea. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…All three fish species usually feed on zooplanktons. However, A. rochei fish also feed on smaller fish, particularly anchovies and also crustaceans [92].…”
Section: Fish Collectionmentioning
confidence: 99%
“…All three fish species usually feed on zooplanktons. However, A. rochei fish also feed on smaller fish, particularly anchovies and also crustaceans [92].…”
Section: Fish Collectionmentioning
confidence: 99%
“…Bullet tuna, classified in the Scombridae family, is an epipelagic fish discovered in worldwide distribution, particularly in tropical waters (Sandoval-Ramírez et al 2020;Mardlijah et al 2021). Furthermore, it is a major target during fishing activities (Ollé-Vilanova et al 2022) and holds high economic value due to its nutritional content. This fish is considered a commodity for export to various countries such as the United States, Japan, Thailand, Italy and Saudi Arabia (Baliwati and Putri 2012) because it possesses high protein content, essential amino acids, unsaturated fats crucial for nutritional needs, growth enhancement, cognitive benefits, cholesterol reduction, and various health advantages (Nepomuceno et al 2020;Rampazzo et al 2020;Wibowo et al 2020;Artetxe-Arrate et al 2021;Husain et al 2021;Bintoro et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Campbell et al [1] showed very high levels of genetic differentiation among populations of Shoshone sculpin Cottus greenei in the Hagerman Valley of Idaho in the western United States; hence, preserving the genetic diversity of this species will require the protection and preservation of multiple isolated populations. Ollé-Vilanova et al [2] showed significant genetic differentiation between an Iberian Peninsula-Strait of Gibraltar stock and North African stocks of bullet tuna Auxis rochei, and suggested that distinct management regimes should be implemented for these two genetic stocks. Nguyen et al [3] found that populations of giant mottled eels A. marmorata in central Vietnam were genetically similar to eels found in North Pacific populations, while those from farther south resembled South Pacific populations, highlighting a combination of differentiated stocks and thus informing fishery management.…”
mentioning
confidence: 99%